Rancang Bangun Mesin Pencacah Untuk Pengolahan Limbah Pertanian Pasca Panen - Harry Prayoga Setyawan (CV. Multi Kreasi Media, 2025)
The agricultural sector faces significant challenges in managing abundant post-harvest residues that have not been optimally utilized. This study aims to design and develop a hammer mill-type agricultural waste shredder with a target capacity of 100 kg/hr to support farmer mobility in local agroclimatic regions. The methodology encompasses 3D model design, technical calculation analysis, and independent manufacturing using mild steel materials. Technical analysis results indicate a design power of 6.72 kW with a torque of 35,653.3 N-mm, powered by a 7.5 HP gasoline engine at 1,800 RPM. Functional testing on rice straw and corn stalks demonstrated operational stability with an actual production capacity reaching ±99.7 kg/hr. A slight mass reduction of approximately 3.5% in the final output was attributed to moisture evaporation caused by mechanical heat during the shredding process. This innovation provides a practical solution for farmer groups in accelerating organic decomposition and improving the efficiency of livestock feed provision.